2019
DOI: 10.1152/ajplung.00551.2017
|View full text |Cite
|
Sign up to set email alerts
|

HDAC8 inhibition ameliorates pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a fibroproliferative lung disease with high mortality, and fibroblast‐myofibroblast differentiation (FMD) is thought to be a key event in the pathogenesis of IPF. Histone deacetylase 8 (HDAC8) has been shown to associate with α‐smooth muscle actin (α‐SMA; a marker of FMD) and regulates cell contractility in vascular smooth muscle cells. However, the role of HDAC8 in FMD or pulmonary fibrosis has never been investigated. This study investigated the role of HDAC8 in pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 53 publications
0
40
0
2
Order By: Relevance
“…Interestingly, we found that knockdown of HDAC7 in the presence of TGFβ also modestly reduced expression of HDAC8 (Fig. S1C), which has previously been shown to drive fibroblast activation in vitro and in vivo (Saito et al, 2019), suggesting an additional target through which HDAC7 may regulate fibroblast activation. HDAC7 knockdown strongly attenuated TGFβ upregulation of fibrosis-associated genes (ACTA2, NOX4 and CTGF) ( Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Interestingly, we found that knockdown of HDAC7 in the presence of TGFβ also modestly reduced expression of HDAC8 (Fig. S1C), which has previously been shown to drive fibroblast activation in vitro and in vivo (Saito et al, 2019), suggesting an additional target through which HDAC7 may regulate fibroblast activation. HDAC7 knockdown strongly attenuated TGFβ upregulation of fibrosis-associated genes (ACTA2, NOX4 and CTGF) ( Fig.…”
Section: Discussionmentioning
confidence: 63%
“…HDAC8 has emerged as an attractive target for isotype‐selective drug development in a variety of diseases, such as cancer, parasitic, and viral infections, as well as neurodegenerative diseases 18 . Despite selective inhibition of HDAC8 with NCC170 has been shown to offer a beneficial effect to pulmonary fibrosis in an animal model of idiopathic pulmonary fibrosis, 45 the role of this enzyme and efficacy of HDAC8 selective inhibitors in other models of diseases associated with tissue fibrosis remain largely unknown. In this work, we demonstrated a remarkable inhibitory effect of PCI34051 on HDAC8, EMT, and renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that pharmacological inhibition of HDACs led to the activation of the peroxisome proliferator-activated receptor (PPAR)γ, a member of nuclear receptors associated with lipogenesis and cell metabolism [18]. In addition, the HDAC8 inhibitor NCC170 was shown to ameliorate idiopathic pulmonary fibrosis, in part, by increasing PPARγ expression [19]. Here, the effect of HMC on PPARγ was assessed using an established PPRE-luciferase reporter assay in MCF7-cells [20].…”
Section: Hmc Inhibits the Akt/mtor Signaling Pathway And Activates Pparγmentioning
confidence: 98%